Pengaruh Suasana Hati terhadap Keaktifan Mahasiswa dalam Kegiatan Organisasi - Muhamad Wahyu Wicaksono; Iqbal Insanul Kamil; Asep Rinda Kramawijaya; Gurawan Dayona Ismail (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The focus of this research is to evaluate the emotional state of students and examine its influence on their participation in organizational activities. This study uses a quantitative method with a correlational approach. In this study, the research subjects consisted of 38 students who were actively involved in campus organizational activities. The sample was taken randomly using a simple method. The data collection technique was through a questionnaire using a Likert scale. The results of the reliability test showed that all the questions posed were valid, while the validity test results showed that the mood variable had a Cronbach's Alpha value of 0.821 which proves that the measuring instrument is reliable. The results of the simple linear regression analysis showed a significance value of 0.004 (p < 0.05) and a regression coefficient of 0.327, indicating that mood has a positive and significant effect. According to this research, a good mood can increase the enthusiasm, motivation, and participation of students in organizational activities.